Ensino Médio e formação para o trabalho na Escola Família Agrícola do Sertão - EFASE - Araújo, Gracieda dos Santos (2022)
This thesis studies the theoretical-methodological conceptions of teaching in the Pedagogy of Alternating Cycle and its unfoldings in the technical and professional formation of rural students, based on the reality of the Escola Família Agrícola do Sertão-EFASE. The entire investigation was guided by the following problem: to what extent does the technical course in agriculture and cattle-raising at EFASE, organized in a regime of Alternating Cycle, contribute to the process of human development of rural students, aiming at their emancipation, in opposition to the forms of education for alienated labor, the predominant perspective in technical education courses? The study starts by defending the access to scientific knowledge, historically produced and systematized by humankind, as an essential task of professional education in the countryside. We observe that in the Agricultural Family Schools (EFAs) that adopt this teaching method, education is based on the Christian humanist thought of Emmanuel Mounier, on the theoretical-philosophical foundations of Piagetian constructivism and the pedagogical theory of the New School of John Dewey, a current linked to the perspective of hegemonic education of the Brazilian Ministry of Education (MEC). Thus, the objective of this research is to discuss the theoretical-philosophical and methodological conceptions of EFASE's Technical High School Course in Agriculture and Livestock Raising, and its contributions to the human development of students from the countryside of the Sisal Territory, in the hinterland of Bahia. To do so, research and study of theoretical and bibliographical references were carried out; document analysis; field work; and listening to the course's graduates, who completed the course between 2009 and 2019. The method adopted as a reference for this investigation is the dialectical historical materialism, for making it possible to understand the world beyond appearances. It is concluded that, although its intention is counter hegemonic, EFASE's theoretical-methodological proposal has a pragmatic, utilitarian educational tendency with little emphasis on classical scientific knowledge. By prioritizing the development of practical skills in the specific areas of the Course, to the detriment of classical scientific knowledge (general academic knowledge), the school indirectly enables the same MEC proposal of pragmatic education, as advocated by international organizations for the education of underdeveloped countries. On the other hand, it is affirmed that the didactic-pedagogical model of the Pedagogy of Alternating Cycle presents itself as a form of education that can be re-signified, based on dialectical historical materialism, due to its proven efficiency in relation to the social practice of the students and their communities.